Reliability and Validity of Walter’s Multiple Intelligences Survey in Pakistan - Tariq, Shah Rukh; Batool, Iffat (Annals of Human and Social Sciences, 2024)
The present research is an effort to a series of psychological assessments of intelligence survey concerning Pakistani cultural contex and assess the reliability and validity of the multiple intelligences survey (MIS) by Walter McKenzie. The cross-sectional research design has been implemented and purposive sampling was utilized to collect participant data. The sample was comprised of BS (Hons.) university students from Punjab, and their age range was 18 years to 24 years (M = 21.18, SD = 2.08). The study consisted of two phases. In phase one data screening and a pilot study were conducted, and in phase two psychometric properties and validity (confirmatory factor analysis) were examined. Findings indicated that the MIS is a reliable and valid instrument. The confirmatory factor analysis emerged nine factors with 41 items. The overall reliability of the MIS was acceptable (α = .88). It has been recommended to explore this construct in-depth. In addition, this instrument could be utilized for screening purposes in educational and psychological assessments.